Perceived benefits and limitations of the SAP system implementation in local government in South Africa - Mutapiri, Pedzisai (My University, 2011)
In order to continuously remain competitive in today‟s information age and global economy, many organisations world-wide have implemented expensive Enterprise Resource Planning (ERP) systems. The difficulties, challenges and critical success factors of implementing ERP systems in organisations have been covered widely in past researches. One area that has not been researched fully yet is the evaluation of the perceived benefits and challenges of ERP systems by the users of the systems long after the implementation projects. This is more so for government organisations in developing countries like South Africa that have also implemented these expensive systems. This research explores and evaluates, by way of a case study, the perceived main benefits and limitations of the implemented SAP system in a local government in South Africa. The research found out that key benefits of ERP systems as perceived by local government SAP users at the Gauteng Provincial Government are: i) Integration of business processes; ii) Automation of business processes; iii) Standardisation of business process; iv) Speeding up of business processes; v) Provision of real-time information; vi) Improvement of customer service; vii) Improvement of corporate governance and transparency; viii)Reduction of IT costs; ix) Improvement of staff motivation; x) Improvement of communication & knowledge sharing; xi) Multi-functional, they cover all business processes; and xii) Improvement of process visibility. iv On the other hand, the research also concluded that the main perceived limitations of the SAP system facing the Gauteng Provincial Government in South Africa are: (i) Expensive to purchase and implement; (ii) Costly to maintain; (iii) High de-investment costs and therefore reduction of flexibility and strategic control; (iv) Shortage of skilled ERP consultants; (v) Interface issues when integrating to other systems; and (vi) Costly academy training fees
MBA - WBS
Keywords: SAP system implementation; Local authorities